Acceptance towards Goods and Services Tax (GST) among local business communities / Shahariah Asmuni, Sabariah Yusoff and Nur Syuhadah Mohd Ses. - Asmuni, Shahariah; Yusoff, Sabariah; Mohd Ses, Nur Syuhadah (Universiti Teknologi Mara Selangor, 2017)
The Goods and Services Tax (GST) has been introduced in Malaysia to replace the Sales and Services Tax (SST) to improve the efficiency of indirect tax collection. However, its implementation has not been fully understood by business people. This research aims to examine the key factors that have contributed to the level of acceptance towards GST among business communities in a local city, Johor Bharu. In this study, three variables were selected namely awareness, understanding and attitude. Using questionnaire as a research instrument, 100 sets of questionnaires were distributed. Multiple regression analysis was used to test the relationship among awareness, understanding and attitude with the level of acceptance among business communities towards GST. The results revealed that the mean score for all independent variables is moderate. Awareness and attitude were found to have significant impact on the level of acceptance among business community towards GST, while understanding is not significant. The business community in Johor Bahru shows a moderate or positive level of acceptance and attitude towards GST.